2022
DOI: 10.1242/dmm.049082
|View full text |Cite
|
Sign up to set email alerts
|

The rat rotenone model reproduces the abnormal pattern of central catecholamine metabolism found in Parkinson's disease

Abstract: Background: Recent reports indicate that Parkinson's disease (PD) involves specific functional abnormalities in residual neurons—decreased vesicular sequestration of cytoplasmic catecholamines via the vesicular monoamine transporter (VMAT) and decreased aldehyde dehydrogenase (ALDH) activity. This double hit builds up the autotoxic metabolite 3,4-dihydroxyphenylacetaldehyde (DOPAL), the focus of the catecholaldehyde hypothesis for the pathogenesis of PD. An animal model is needed that reproduces this abnormal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
3
6
0
Order By: Relevance
“…Recently, we analyzed the striatal neurochemical profile following systemic administration of rotenone to Sprague Dawley rats, a well-established animal model of Parkinson's disease [21][22][23]. Rotenone caused striatal depletion of dopamine, increased striatal DOPAL, and induced the double hit of decreased vesicular sequestration and decreased ALDH activity [24]. We therefore concluded that the rat rotenone model replicates the changes found in humans and is in line with the neurochemical profile that underlies the catecholaldehyde hypothesis.…”
Section: The Molecular Basis Of the Catecholaldehyde Hypothesissupporting
confidence: 53%
“…Recently, we analyzed the striatal neurochemical profile following systemic administration of rotenone to Sprague Dawley rats, a well-established animal model of Parkinson's disease [21][22][23]. Rotenone caused striatal depletion of dopamine, increased striatal DOPAL, and induced the double hit of decreased vesicular sequestration and decreased ALDH activity [24]. We therefore concluded that the rat rotenone model replicates the changes found in humans and is in line with the neurochemical profile that underlies the catecholaldehyde hypothesis.…”
Section: The Molecular Basis Of the Catecholaldehyde Hypothesissupporting
confidence: 53%
“…A vesicular storage defect would not only deplete releasable neurotransmitter stores but also promote autotoxicity from augmented oxidation of cytoplasmic catecholamines ( 37 39 ). Diminished vesicular storage in existing nerve terminals could have any of several causes, such as decreased mitochondrial complex 1 activity ( 40 ), α-synuclein (αS) oligomers ( 37 , 41 ), or decreased VMAT2 availability ( 42 ), all of which are potential therapeutic targets; however, no previous study has determined whether indices of attenuated vesicular sequestration in cardiac sympathetic nerves precede central LBDs in at-risk individuals.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo experimental model shows RO induces loss of dopaminergic neurons in the substantia nigra, one of the characteristic features of PD neuropathology. 86 Rotenone also replicates the clinical features of PD, including the aggregation of α-synuclein and the formation of Lewy bodies. 87 …”
Section: Mitochondrial Toxicants and Neurodegenerationmentioning
confidence: 85%